PENGARUH VOLUME LALU LINTAS TERHADAP TINGKAT KBISINGAN PADA JALAN Dr. SOETOMO - KADRI, MUHAMMAD HUSIN (KURVA S JURNAL MAHASISWA, 2016)
An uproar is the hopeless voice and this voice disturbs people, even, in several cases it can cause an accident. Hospital is one of public facilities that is used for caring, improving and giving treatment to humanâ€™s health.Â  PROF DR, Tabrani Rab hospitals serve many patients with variant of illnesses. It means that there will be many patients that are cared in these hospitals. A patient, of course, needs calm and quiet condition for getting treatment his illness. On the other hand, the location of the three hospitals above is near the traffic road, therefore they get impact from the traffic current in those roads, namely; an uproar. According to Slater (1985), the counting of uproar caused by traffic current can be counted by applying the following formula: L10 18h = 29,1 + 10 log Q dBA or L10 = 42,2 + 10 log Q dBA. The highest level of uproar is 73 dB(A) that happens, meanwhile the lowest level of uproar is 66 dB(A) that happens in hospital. In accordance with the rule of Environmental Ministry, the level of uproar in hospital should not be more than 55 dB(A). It means that the location of the three hospitals in Pekanbaru does not fulfill the requiement for activities related with health. Therefore, they must reduce the voice sources that can meke uproar.